Perencanaan Sistem Penyediaan Air Bersih Di Dusun Tapi Kecamatan Leihitu Barat - Gamarullaila Tuhelelu; Renny James Betaubun (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to (1) Find out the availability and need for clean water in Tapi Hamlet (Lorong Madu) (2) Find out the capacity of clean water discharge that can be used to meet the needs of the community in Tapi Hamlet (Lorong Madu) (3) Find out how much water is needed for Projection of population in the next 10 years in Tapi Hamlet (Lorong Madu). The method used in this research is quantitative. The results of the research are that the availability of water in Tapi Hamlet (Lorong Madu) is very sufficient, and the water requirement for Tapi Hamlet (Lorong Madu) is 4560 liters/day. From the calculation results it was found that the availability of water discharge was 0.0625 m3/second which apparently was sufficient for the planned water discharge requirement, namely 0.000009 liters/second (0.0000000009 m3/second). From the calculation results the population of Tapi Hamlet for the next 10 years from 2021 to 2031 for 57 people is 4560 liters/day (0.53 liters/second).